Physical activity, Vitamin D, and all-cause/cardiovascular mortality: a prospective study in older Chinese adults - Mingrui Chen; Ling Cheng; Sisi Yang; Yan Zhang (BMC Geriatrics)
Abstract Background Physical activity was associated with the risk of all-cause and cardiovascular mortality. However, little is known about older adults, especially those aged over 80 years. Methods 2863 older adults in the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were enrolled. Physical activity score was used to evaluate the physical activity. Serum 25-hydroxyvitamin D and demographic characteristics were collected at baseline. We used multivariable-adjusted Cox regression models and stratified analysis to determine the association between physical activity, vitamin D and all-cause/cardiovascular mortality. Mediation analysis was performed to evaluate the mediating effect of vitamin D between physical activity and all-cause/cardiovascular mortality. Results The median age of this population was 87 years, and 70.27% were the oldest-old (age ≥ 80 years). We observed a tendency for a higher vitamin D concentration in participants with higher physical activity score levels. Both physical activity and vitamin D levels were inversely associated with all-cause and cardiovascular mortality in all participants. Between physical activity and all-cause/cardiovascular mortality, the mediation proportions of vitamin D were 7.76% (P < 0.001) and 4.13% (P < 0.001), respectively. The mediating effect of vitamin D remained all significant in various types of physical activities. Furthermore, vitamin D accounted for a greater mediating proportion in the physical activities of housework and raising domestic animals/pets. Conclusions Physical activity could reduce the risk of all-cause/cardiovascular mortality and was mediated by vitamin D in older Chinese adults.